The BioExperience Research and Entrepreneurship Challenge: An iGEM-inspired applied research program for BIOSTEM talent and skills development - Gill, Hertek; Ahsan, Mahdi; Khalil, Yara; Feng, Victoria; Pearce, Jessie; Sharma, Tarasha; Radwan, Mohamad; Boucinha, Austin; Kærn, Mads (Frontiers in Bioengineering and Biotechnology, 2022)
Post-secondary education is falling behind in delivering the talent and skills development needed to support the growth of biology-based economies and the demands of professional and research-based graduate degree programs. Here, we describe the BioExperience Research and Entrepreneurship Challenge, a student-centred applied research program for undergraduate talent and skills development. The BioExperience program was created in April, 2020 to mitigate the impact of the COVID-19 pandemic on undergraduate experiential learning at the University of Ottawa, Ontario, Canada. We present evidence suggesting it delivers improved learning outcomes than conventional work-integrated learning programs by implementing a student-centred, project-based learning approach. This approach was inspired by the international Genetic Engineering Machines (iGEM) competition, whereby undergraduates from different disciplines and academic levels work in teams to complete an applied research project throughout the summer. The analyses of participant exit surveys suggest that the BioExperience program delivers an outstanding learning experience and facilitates significant gains in skills and abilities that are difficult to acquire in conventional academic programs, such as critical thinking, problem-solving, communication, adaptability, and research preparedness. A majority of students report that the program provides superior learning opportunities than traditional work-integrated learning, such as research internships and cooperative learning placements. These findings indicate that the implementation of the BioExperience or similar programs at post-secondary institutions could improve talent and skills development in the BIOSTEM fields of bioscience, biotechnology, bioengineering and biomedicine.